Kieli avaimena muuttuvaan maailmaan - Veivo, Outi; Jakonen, Teppo; Laine, Päivi; Merke, Saija (Suomen Soveltavan Kielitieteen Yhdistys AFinLA ry, 2026)
The theme of the AFinLA Autumn Symposium in 2024 was Language as a Key to a Changing World. It reflects an era of ongoing societal transformation shaped by rapid technological development, the escalating climate crisis, increasing geopolitical tensions, and growing social inequality, factors which place pressure on societies. This introductory article explores the symposium theme in relation to recent directions in applied linguistics and presents the articles included in this yearbook. This article discusses how applied linguistics can help us understand complex processes of societal change and actively contribute to shaping those processes through critical engagement and interdisciplinary collaboration. It sheds light on the possibilities that collaborative work within the field of applied linguistics offers for researching and addressing these interconnected challenges. By reflecting on recurring themes in the 2024 Symposium, the article highlights the ways in which language serves to connect and divide people, construct communities, and produce or reinforce structures of equality and inequality.
AFinLAn vuosikirja: Kieli avaimena muuttuvaan maailmaan